Complexation and Extraction of Transition Metal Cations by New Azodyes: Synthesis, Structure Elucidation and Binding Properties - Naouali, Olfa; Mellah, Besma; Ternane, Riadh; Baklouti, Lassaad; Hamdi, Abdelwaheb; Hamdi, Naceur (Asian Journal of Chemistry, 2018)
A series of new 3-aryl(hetaryl)hydrazono-2,4-chromandiones (3a-c) were obtained in high yields, by coupling 4-hydroxycoumarin with derivatives diazonium salts, which were obtained by diazotization of aniline derivatives in presence of sodium nitrite and concentrated HCl. The azo dyes prepared may exist in four tautomeric forms. Structures of the synthesized compounds have been investigated by means of UV, IR, 1H NMR, 13C NMR and elemental analysis in order to elucidate their tautomeric and isomeric structures. The results of such spectral data indicated that compound 3 exist predominantly in hydrazo structure (D). The complexation and extraction of some transition metal cations have been followed by UV-visible spectrophotometry absorption. The conductivity studies have been used in order to confirm complex’s stoichiometries.